Estruturação do Ceatenf - Fonteles, Marta Maria de França; Moreira, Luzia Izabel Mesquita; Romero, Nirla Rodrigues; e Reis, Henry Pablo Lopes Campos; Ponciano, Ângela Maria de Souza (Experiências Exitosas de Farmacêuticos no SUS, 2015)
Estruturação do Ceatenf